Hardiness Dan Stress Akademik Pada Mahasiswa Rantau - Agustina, Mirna Wahyu; Putri Deastuti, Pracintya Wahyu (IDEA: Jurnal Psikologi, 2023)
Overseas students are students who study in a different place from their place of origin. Overseas students tend to face more serious problems than non-overseas students and also different psychological pressures, one of which is academic stress. Meanwhile, hardiness is needed to minimize academic stress on overseas students. This study aims to determine the effect of hardiness on academic stress in overseas students. This research was conducted on overseas students of UIN Sayyid Ali Rahmatullah class of 2019 until 2022. The number of samples in this study was 384 respondents. This research is research using quantitative methods with a comparative causal approach. The sampling technique in this study used a purposive sampling technique. Meanwhile, the data collection used in this study used a hardiness scale and an academic stress scale which were tested by validity and reliability tests. The data analysis technique in this study used simple regression assisted by SPSS V 22. From the research results obtained by the researcher, it is known that the results of the regression are p = 0.001 which is symbolized by p <0.05 and the R Square value is 0.27 or 2, 7%. The results in this study indicate that the hypothesis that has been proposed is accepted, namely that there is an effect of hardiness on academic stress in UIN Sayyid Ali Rahmatullah Tulungagung overseas students with a negative significance direction.